Sorafenib-Induced Pancreatitis - Ayyildiz, T.; Aydın, T.; Eminler, A.T.; Yıldırım, C.; Irak, K.; Kıyıcı, M.; Gürel, S. (Ondokuz Mayis Universitesi Samsun 55139, 2015)
Sorafenib is an inhibitor of multikinase proteins which is used for metastatic renal cell carcinoma and advanced stage hepatocellular carcinoma. Its side effects include serum amylase and lipase elevations anticipated to occur within first weeks of treatment but clinically and radiologically evident acute pancreatitis develops rarely. Five cases of acute pancreatitis have been reported in literature until date. The case we described here is the sixth case of clinically diagnosed acute pancreatitis. © 2015 OMU.
Keywords: Hepatocellular Carcinoma; Pancreatitis; Sorafenib; Tyrosine Kinase Inhibitor